SIMULATION-BASED ANALYSIS FOR OPTIMIZING MOLD DESIGN OF PLASTIC HARDNESS TEST SPECIMENS USING KEY PARAMETERS - Pujo Leksonowati, Nur Fitria; Pamungkas, Nurman; Manurung, Meilani; Aryswan, Adhe; Hakim, Rahman; Stefani, Windy; Purba, Adi; Khollilurrahman, Kholillurrahman; Batubara, Ninda (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
This study aims to compare the performance of two injection molding designs—Design A and Design B—for producing plastic hardness test specimens. Design A showed a fill time of 1.03 s and cooling quality covering 84.2% of the part, compared to 1.06 s and 72.4% for Design B. Design B, however, exhibited deflection of 0.96 mm versus 1.15 mm for Design A, and a maximum sink mark depth of 0.5687 mm versus 0.5773 mm. These characteristics in Design B support dimensional stability and limit visible defects, making it suitable for fabrication. Optimization strategies, such as adjustments to packing pressure, gate location, and the cooling system, are proposed to improve Design B's performance in terms of production efficiency and quality. The results indicate that, despite advantages in Design A, Design B offers a viable option for large-scale injection molding, balancing quality and operational efficiency.